Theory Semiring_Normalization

(*  Title:      HOL/Semiring_Normalization.thy
    Author:     Amine Chaieb, TU Muenchen
*)

section Semiring normalization

theory Semiring_Normalization
imports Numeral_Simprocs
begin

text Prelude

class comm_semiring_1_cancel_crossproduct = comm_semiring_1_cancel +
  assumes crossproduct_eq: "w * y + x * z = w * z + x * y  w = x  y = z"
begin

lemma crossproduct_noteq:
  "a  b  c  d  a * c + b * d  a * d + b * c"
  by (simp add: crossproduct_eq)

lemma add_scale_eq_noteq:
  "r  0  a = b  c  d  a + r * c  b + r * d"
proof (rule notI)
  assume nz: "r 0" and cnd: "a = b  cd"
    and eq: "a + (r * c) = b + (r * d)"
  have "(0 * d) + (r * c) = (0 * c) + (r * d)"
    using add_left_imp_eq eq mult_zero_left by (simp add: cnd)
  then show False using crossproduct_eq [of 0 d] nz cnd by simp
qed

lemma add_0_iff:
  "b = b + a  a = 0"
  using add_left_imp_eq [of b a 0] by auto

end

subclass (in idom) comm_semiring_1_cancel_crossproduct
proof
  fix w x y z
  show "w * y + x * z = w * z + x * y  w = x  y = z"
  proof
    assume "w * y + x * z = w * z + x * y"
    then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
    then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
    then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
    then have "y - z = 0  w - x = 0" by (rule divisors_zero)
    then show "w = x  y = z" by auto
  qed (auto simp add: ac_simps)
qed

instance nat :: comm_semiring_1_cancel_crossproduct
proof
  fix w x y z :: nat
  have aux: "y z. y < z  w * y + x * z = w * z + x * y  w = x"
  proof -
    fix y z :: nat
    assume "y < z" then have "k. z = y + k  k  0" by (intro exI [of _ "z - y"]) auto
    then obtain k where "z = y + k" and "k  0" by blast
    assume "w * y + x * z = w * z + x * y"
    then have "(w * y + x * y) + x * k = (w * y + x * y) + w * k" by (simp add: z = y + k algebra_simps)
    then have "x * k = w * k" by simp
    then show "w = x" using k  0 by simp
  qed
  show "w * y + x * z = w * z + x * y  w = x  y = z"
    by (auto simp add: neq_iff dest!: aux)
qed

text Semiring normalization proper

ML_file Tools/semiring_normalizer.ML

context comm_semiring_1
begin

lemma semiring_normalization_rules [no_atp]:
  "(a * m) + (b * m) = (a + b) * m"
  "(a * m) + m = (a + 1) * m"
  "m + (a * m) = (a + 1) * m"
  "m + m = (1 + 1) * m"
  "0 + a = a"
  "a + 0 = a"
  "a * b = b * a"
  "(a + b) * c = (a * c) + (b * c)"
  "0 * a = 0"
  "a * 0 = 0"
  "1 * a = a"
  "a * 1 = a"
  "(lx * ly) * (rx * ry) = (lx * rx) * (ly * ry)"
  "(lx * ly) * (rx * ry) = lx * (ly * (rx * ry))"
  "(lx * ly) * (rx * ry) = rx * ((lx * ly) * ry)"
  "(lx * ly) * rx = (lx * rx) * ly"
  "(lx * ly) * rx = lx * (ly * rx)"
  "lx * (rx * ry) = (lx * rx) * ry"
  "lx * (rx * ry) = rx * (lx * ry)"
  "(a + b) + (c + d) = (a + c) + (b + d)"
  "(a + b) + c = a + (b + c)"
  "a + (c + d) = c + (a + d)"
  "(a + b) + c = (a + c) + b"
  "a + c = c + a"
  "a + (c + d) = (a + c) + d"
  "(x ^ p) * (x ^ q) = x ^ (p + q)"
  "x * (x ^ q) = x ^ (Suc q)"
  "(x ^ q) * x = x ^ (Suc q)"
  "x * x = x2"
  "(x * y) ^ q = (x ^ q) * (y ^ q)"
  "(x ^ p) ^ q = x ^ (p * q)"
  "x ^ 0 = 1"
  "x ^ 1 = x"
  "x * (y + z) = (x * y) + (x * z)"
  "x ^ (Suc q) = x * (x ^ q)"
  "x ^ (2*n) = (x ^ n) * (x ^ n)"
  by (simp_all add: algebra_simps power_add power2_eq_square
    power_mult_distrib power_mult del: one_add_one)

local_setup 
  Semiring_Normalizer.declare @{thm comm_semiring_1_axioms}
    {semiring = ([termx + y, termx * y, termx ^ n, term0, term1],
      @{thms semiring_normalization_rules}),
     ring = ([], []),
     field = ([], []),
     idom = [],
     ideal = []}


end

context comm_ring_1
begin

lemma ring_normalization_rules [no_atp]:
  "- x = (- 1) * x"
  "x - y = x + (- y)"
  by simp_all

local_setup 
  Semiring_Normalizer.declare @{thm comm_ring_1_axioms}
    {semiring = ([termx + y, termx * y, termx ^ n, term0, term1],
      @{thms semiring_normalization_rules}),
      ring = ([termx - y, term- x], @{thms ring_normalization_rules}),
      field = ([], []),
      idom = [],
      ideal = []}


end

context comm_semiring_1_cancel_crossproduct
begin

local_setup 
  Semiring_Normalizer.declare @{thm comm_semiring_1_cancel_crossproduct_axioms}
    {semiring = ([termx + y, termx * y, termx ^ n, term0, term1],
      @{thms semiring_normalization_rules}),
     ring = ([], []),
     field = ([], []),
     idom = @{thms crossproduct_noteq add_scale_eq_noteq},
     ideal = []}


end

context idom
begin

local_setup 
  Semiring_Normalizer.declare @{thm idom_axioms}
   {semiring = ([termx + y, termx * y, termx ^ n, term0, term1],
      @{thms semiring_normalization_rules}),
    ring = ([termx - y, term- x], @{thms ring_normalization_rules}),
    field = ([], []),
    idom = @{thms crossproduct_noteq add_scale_eq_noteq},
    ideal = @{thms right_minus_eq add_0_iff}}


end

context field
begin

local_setup 
  Semiring_Normalizer.declare @{thm field_axioms}
   {semiring = ([termx + y, termx * y, termx ^ n, term0, term1],
      @{thms semiring_normalization_rules}),
    ring = ([termx - y, term- x], @{thms ring_normalization_rules}),
    field = ([termx / y, terminverse x], @{thms divide_inverse inverse_eq_divide}),
    idom = @{thms crossproduct_noteq add_scale_eq_noteq},
    ideal = @{thms right_minus_eq add_0_iff}}


end

code_identifier
  code_module Semiring_Normalization  (SML) Arith and (OCaml) Arith and (Haskell) Arith

end